2023
DOI: 10.1021/jacs.2c11787
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally Long Lifetimes of Strongly Entangled Acyl–Trityl Radical Pairs Photochemically Generated in Crystalline Trityl Ketones

Abstract: Triplet acyl–alkyl radical pairs generated by pulsed laser excitation within the constraints of their nanocrystalline ketone precursors were recently introduced as a potential platform for the robust and repeated instantiation of spin qubit pairs for applications in quantum information science. Here, we report the transient spectroscopy of a series of nanocrystalline trityl–alkyl and trityl–aryl ketones capable of generating correlated triplet radical pairs with persistent triphenylmethyl radicals forced to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Having confirmed that the reaction in nanocrystals proceeds through the mechanism described in Scheme 1, we identified four species that could potentially be observed through laser flash photolysis: the triplet ketone ( 3 K), the individual ketyl and benzyl radicals in solution, and the triplet radical pair 3 As shown in Figure 2, the absorbance values of the solutionphase spectra closely resemble the triplet ketone reported by Tsubomura et al, with two broad peaks centered around 330 and 540 nm and a smaller transition at ca. 410 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Having confirmed that the reaction in nanocrystals proceeds through the mechanism described in Scheme 1, we identified four species that could potentially be observed through laser flash photolysis: the triplet ketone ( 3 K), the individual ketyl and benzyl radicals in solution, and the triplet radical pair 3 As shown in Figure 2, the absorbance values of the solutionphase spectra closely resemble the triplet ketone reported by Tsubomura et al, with two broad peaks centered around 330 and 540 nm and a smaller transition at ca. 410 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…100–300 nm) are amenable for the use of transmission spectroscopy . Previous investigations into the kinetics of solid state photochemical reactions have primarily focused on intramolecular processes, such as the Norrish Type-I , and Type-II reactions. Looking to establish and expand the scope of the method, we identified the radical-pair-mediated dimerization of 4,4′-dimethylbenzophenone ( DMBP ) reported by Ito and co-workers, as a suitable system …”
Section: Introductionmentioning
confidence: 99%
“…61 Therefore, the species with lifetimes in microseconds assigned to 5a-RP decay unprecedentedly slowly for a singlet radical pair. Long-lived singlet radical pairs have been detected in viscous solvent, 62 and there are rare examples of long-lived singlet 1,3-biradicals (τ > 10 μs), which are stabilized by πsingle bonds, 63 biradicals detected in microcrystalline suspensions, 64 or in cryptochromes (flavoproteins involved in the repair of UV light-induced DNA damage) of migrating birds. 65 Consequently, the transients detected by fs-TA indeed correspond to the tight radical pair, whereas the species detected on the longer time scale in microseconds are probably benzyl radicals that underwent solvent separation and/or cage escape.…”
Section: Investigation Of Photochemical Reaction Mechanismmentioning
confidence: 99%